Burden of COVID-19 on primary care in Belgium: a prospective nationwide observational study from March to August 2020 - Bert Vaes; Bénédicte Vos; Maxime Foidart; Robrecht De Schreye; Diego Schrans; Hilde Philips; Bert Aertgeerts; Kris Doggen (BMC, 2022)
Abstract Background The COVID-19 outbreak had an important impact on general practice, for example the lack of personal protective equipment (PPE) and the switch to telephone consultations. We installed a monitoring instrument and reported the burden the COVID-19 pandemic placed on Belgian general practitioners (GPs) during the first wave of the pandemic. Methods We conducted an observational longitudinal prospective study from the 19th of March until the 17th of August 2020. Daily data were collected by using a structured electronic form integrated into the GPs' electronic medical records (EMRs). Data were collected on the GPs' need for support and workload, epidemiological indicators and the availability of PPE. Reports with graphical presentations were made for GP circles and primary care zones, and governments of different administrative levels had access to all data to guide their policy. Results A total of 3.769 different GP centres participated, which included more than 10.000 GPs. Throughout the first three weeks, 20% declared they had insufficient resources (personnel and material) for the following week. Approximately 10% continued to report this during the entire study. The majority reported being able to complete their daily tasks without loss of quality. During the first week, 30% indicated an increased workload. Afterwards, this number decreased and stabilized to an average of 10-20%. More than 70% of the consultations in March 2020 were conducted by telephone. This percentage declined in April and stabilized at approximately 30% in June 2020. Consultations due to respiratory symptoms peaked at 4000/100,000 inhabitants at the beginning of the outbreak, then decreased over time along with the COVID-19 incidence. We noticed a lack of disinfectant hand gel, surgical masks and FFP2 masks, the latter remaining problematic in the long term. Conclusion We introduced an instrument in Belgian EMR systems to monitor the burden on GPs during the first wave of the COVID-19 pandemic. The lack of PPE and increased workload were considered to be the main obstacles. A large number of the GP offices switched to teleconsultations to provide healthcare. Our monitoring instrument provided information for policy makers to intervene on a local level.